Blessed be the surgeon?: the Lubavitcher Rebbe, the Emuna u-mada' controversy and its legacy - Tarant, Zbyněk (Religio, 2021)
This article analyzes the intellectual controversy sparked by the remarks of the last Rebbe of the Lubavitcher dynasty, Menachem Mendel Schneerson (1902-1994), concerning the alleged Divine role in the horrors of the Shoah in the 1970s. The ensuing dispute took place in the form of essays, newspaper articles and op-eds, as well as private and open letters, and its echoes have occasionally resonated well into the 2000s. Closer inspection of the controversy, offered in this article, reveals not only the conflicting paradigms between traditional Jewish theodicy on the one hand and secular ethics on the other, but also the differences between Ḥaṣidic hagiographic narration and scientific positivism. This article analyzes the entire debate by using original Hebrew sources, some of which have never been published in English. The Rebbe's controversial words are analyzed in their full, original context, and the ensuing controversy is explored with a focus on the incompatible patterns of reasoning that may have hindered the dialogue. By further exploring the legacy of this controversy, the article also serves as a case study on how apocrypha are construed in contemporary religious movements.